Genetic polymorphisms of the ABO blood group system in patients with myeloid leukemia (Journal of the College of Basic Education, 2022)
The ABO blood group system was genotyped in a sample of 145 individuals with myelogenous leukemia. This sample was divided into a group of 80 individuals with chronic myelogenous leukemia, as well as a group of 65 individuals with acute myelogenous leukemia, while the standard sample included 100 individuals. The aim of the current study is to investigate whether there is a relationship between the frequency of ABO phenotypes and susceptibility to myelogenous leukemia compared to the standard sample, in addition to determining the genetic frequency of the ABO groups in the studied samples. The results of the different comparisons between patient samples and the standard sample in the frequency of these groups showed that there were no significant differences, as well as the results of genetic repetitions, which indicate that there is no deviation from the expected numbers according to Hardy / Weinberg law.